2016
DOI: 10.5055/jem.2014.0182
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Reverse 911®: A case study of the 2007 San Diego wildfires

Abstract: In October 2007, 250,000 residents of San Diego County were forced to evacuate as wildfires burned 62 miles(2) in 24 hours. In 2005, the Sheriff's Department invested in Reverse 911® to contact residents upon emergencies. The system was used during this wildfire, and by the following midday, had made 394,915 calls. Shortly thereafter, 1,210 residents were surveyed to investigate the effectiveness of this technology. Findings reveal that 42 percent of respondents received their first warning from a Reverse 911®… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Forty papers were found that provided information pertinent to communication and public action during natural disasters. Twenty-one publications relate to the origin and media form, with thirteen providing information on traditional media [9][10][11][12][13][14][15][16][17][18][19][20][21], eleven on nontraditional sources [10,11,15,[20][21][22][23][24][25][26][27], and seven on choice of media [9][10][11]15,18,28,29]. Five articles provided information on smoke avoidance behaviours [19,20,22,25,30,31].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Forty papers were found that provided information pertinent to communication and public action during natural disasters. Twenty-one publications relate to the origin and media form, with thirteen providing information on traditional media [9][10][11][12][13][14][15][16][17][18][19][20][21], eleven on nontraditional sources [10,11,15,[20][21][22][23][24][25][26][27], and seven on choice of media [9][10][11]15,18,28,29]. Five articles provided information on smoke avoidance behaviours [19,20,22,25,30,31].…”
Section: Resultsmentioning
confidence: 99%
“…During disasters, social media platforms have been found to dominate disaster communication channels with content such as warnings, imagery, help requests, health communication, coordination of aid relief, and communication of safety status [15]. When alerting communities of the need to evacuate, most reports came through telephone calls, with other media forms including television, radio, door-to-door knocks, and wordof-mouth [10,28]. Reverse emergency calls were found to be useful in the United States of America as emergency organisations were able to contact residents who may be in danger more directly [28].…”
Section: Communication Mediamentioning
confidence: 99%
See 3 more Smart Citations